1980
DOI: 10.1002/bjs.1800670119
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bile salts on the pancreatic duct mucosal barrier

Abstract: The effects of various bile salts on the permeability of the pancreatic duct in cats have been investigated. The sodium salts of cholic, glycocholic, taurocholic, chenodeoxycholic, glycochenodeoxycholic, deoxycholic and glycodeoxycholic acids were perfused through the main duct in concentrations similar to those found in the duodenal contents (15-42 mM). HCO3- and Cl- fluxes were determined before and after perfusion. The unconjugated dihydroxy bile salts increased permeability to these anions to a greater deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The issue is far from resolved, since some studies question the role of bile in the pathology of acute pancreatitis (60,61). However, bile acids have a drastic effect on the permeability of the pancreatic duct mucosal barrier (62), and two recent studies demonstrated that bile acids are capable of inducing sustained toxic calcium signals in pancreatic acinar cells (20,44).…”
Section: Discussionmentioning
confidence: 99%
“…The issue is far from resolved, since some studies question the role of bile in the pathology of acute pancreatitis (60,61). However, bile acids have a drastic effect on the permeability of the pancreatic duct mucosal barrier (62), and two recent studies demonstrated that bile acids are capable of inducing sustained toxic calcium signals in pancreatic acinar cells (20,44).…”
Section: Discussionmentioning
confidence: 99%
“…Although bile acids can cause some change in the permeability of the pancreatic duct mucosal barrier (42), their major effects appear to occur on the pancreatic acinar cell, the initiating site for pancreatitis. One of the earliest pathological changes observed in the acinar cell is the emergence of high-amplitude, globalized cytosolic Ca 2ϩ signals (40).…”
mentioning
confidence: 99%
“…At severely low [ATP] the Cl − /HCO 3 − exchanger function is suppressed. As a consequence, low fluid secretion rate favors ductal cell injury and the damage of ductal integrity, thus acute pancreatitis [31,[33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%